Using R to Apply Open Science Principles in Second Language Acquisition and Didactics - Marie-Pierre Jouannaud (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In this article, the advantages of the Open Science movement in terms of open access to publications and results, collaboration between researchers, and especially methodological transparency, are presented. It is then argued that the R software is a useful tool which can contribute to the sharing of data analysis methods by providing explicit information about the pre-treatment of data files and the statistical analyses used. R also helps with the comprehension of results by facilitating the production of data-accountable graphics. This is illustrated in the context of a large-scale research project requiring the use of statistics to analyze data from pre- and post-tests to validate the use of Luciole, an educational app teaching English listening comprehension in first- and second-grade classrooms in France.